Official Financing : Recent Developments and Selected Issues. (World Economic and Financial Surveys; World Economic and Financial Surveys, 2004)
This study provides information on official financing and the debt situation of developing countries. It discusses issues related to trade finance in financial crises, and the challenge of maintaining external debt sustainability in debtor countries. It updates the 2001 edition of Official Financing for Developing Countries.